Computer aided simulation POME biogas purification system - Yap, Andrew Kian Chung; Ummi Kalsum Hasanah M.N (Penerbit Universiti Kebangsaan Malaysia, 2021)
About three (3) tonnes of palm oil mill effluent (POME) is generated when one (1) tonne of crude palm oil (CPO) is produced. Microbial digestion treatment is commonly used in Malaysian palm oil mills due to the low capital expenditure (CAPEX) and operational expenditure (OPEX). However, anaerobic digestion of POME produces methane gas which is 21 times more harmful than carbon dioxide. 1m3 of POME could generate 27m3of biogas at standard temperature and pressure with approximate caloric value of 20 MJm-3 under optimum conditions Thus, methane capturing biogas plant to address sustainability issue is included as part of effluent treatment plant. Many mills start to utilise the biogas energy to replace palm kernel shell which could be sold as renewable solid fuel. Although untreated biogas may be good enough for boiler fuel, internal combustion engines need a fairly homogeneous fuel with methane (CH4) content up to 80 % and hydrogen sulphite (H2S) content less than 200 ppm in order to ensure the optimum engine performance. Water scrubber system is widely used in gas purification. Computer aided biogas purification system simulation involving water scrubber and flashing drum is presented in the effort to produce IC engine fuel. ChemCAD simulation result shows that POME biogas purification process is feasible at 10 bar pressure and 25°C ambient temperature.